Reducing bias and increasing surgical knowledge: multicentre prospective breast cancer studies. Issue 3 (6th March 2021) - Sund, M
Abstract: In the March issue of BJS several hot topics within the breast surgery field are highlighted in beautifully planned and executed prospective multicentre trials. BJS encourages the surgical communities in most fields to move towards prospective collaborative and multicentre studies, thereby increasing both power and generalizability as well as reducing the risk of bias.